2020
DOI: 10.3389/fpls.2020.00593
|View full text |Cite
|
Sign up to set email alerts
|

PhenoCams for Field Phenotyping: Using Very High Temporal Resolution Digital Repeated Photography to Investigate Interactions of Growth, Phenology, and Harvest Traits

Abstract: Understanding the interaction of plant growth with environmental conditions is crucial to increase the resilience of current cropping systems to a changing climate. Here, we investigate PhenoCams as a high-throughput approach for field phenotyping experiments to assess growth dynamics of many different genotypes simultaneously in high temporal (daily) resolution. First, we develop a method that extracts a daily phenological signal that is normalized for the different viewing geometries of the pixels within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 96 publications
1
24
0
Order By: Relevance
“…The results of the subsequently conducted Dunnett test confirmed that the determination of VCOV traits was possible through the use of drone-mounted RGB cameras and that the accuracy of the results was sufficient for further quantitative genetic analysis. However, the results presented here were severely limited by the number of observations at the time of the trait increase, because to extract growth dynamics from imagery data, temporally high-resolution data collection is critical [20]. The weekly trait monitoring of the environments resulted in only 2-3 relevant observations that could be used for growth modelling until saturation was reached, which was not sufficient to detect the small trait variations within the population.…”
Section: Vegetation Covermentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the subsequently conducted Dunnett test confirmed that the determination of VCOV traits was possible through the use of drone-mounted RGB cameras and that the accuracy of the results was sufficient for further quantitative genetic analysis. However, the results presented here were severely limited by the number of observations at the time of the trait increase, because to extract growth dynamics from imagery data, temporally high-resolution data collection is critical [20]. The weekly trait monitoring of the environments resulted in only 2-3 relevant observations that could be used for growth modelling until saturation was reached, which was not sufficient to detect the small trait variations within the population.…”
Section: Vegetation Covermentioning
confidence: 99%
“…Breeding selection at this early stage of the breeding cycle is based on a few rapidly collected traits and thus offers the most potential for improvement through a better phenotype database provided by UAV. The high temporal resolution enables the observation of dynamic growth processes and the detection of small phenotypic differences and thus the extraction of new traits regarding plant architecture and physiology [20,21]. In order to make optimal use of time series of measurements and to characterize dynamic growth, it is essential to carry out functional analyses in which mathematical functions are able to simulate the plant growth pattern [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Optimum planting geometry can be employed for the reduction of harmful effects on phenology due to climate change. Plant phenology is also affected by planting geometry 130 , 249 . Crop microclimate is changed by varying planting geometry like planting density, row spacing, seed rate etc.…”
Section: Adaptation Strategies In Response To Climate Changementioning
confidence: 99%
“…For example, GCC has been found to be in good agreement with start-of-season and end-of-season indicators for honey mesquite, but not black grama; for both species it correlated well with canopy greenness [22]. However, [5] and [23] have found there is not a reliable direct correlation between LAI and GCC.…”
Section: Data Acquisition For Images and Gccmentioning
confidence: 94%
“…In a 2020 study, Aasen et al [23] determined there was not a clear correlation between GCC and LAI however, they were able to track LAI development using the PhenoCams. While we agree there is no universal GCC and LAI relationship, our methods adapted to each site and species do allow for LAI to be determined using PhenoCams.…”
Section: Jersand Nm: Creosote Bushmentioning
confidence: 99%